To Kill or Not to Kill - the Use of Force against Legitimate Targets in Armed Conflicts - Grzebyk, Patrycja (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Armed conflicts involve killing, injuring, devastating. The International Humanitarian Law (IHL) accepts this reality, but limits the categories of persons and objects which can be attacked, as well as the means and methods by which they can be attacked. The aim of this chapter is threefold. Firstly, it is to present arguments derived from the IHL norms against the existence of an obligation to use the least harmful method against legitimate targets in armed conflicts. Secondly, it is to assess the argumentation (also based on the IHL) in favour of the existence of an obligation to minimize force used against legitimate targets. In both cases, advantages and disadvantages of each of the solutions will be presented. Thirdly, it is to assess the possibility of using other regimes to solve the dispute between two above-mentioned approaches.
Keywords: konflikty zbrojne; międzynarodowe prawo humanitarne; prawnie uzasadnione cele